Analisis Keputusan Pembelian Kuliner Ayam Betutu pada Ayam Betutu Khas Gilimanuk Renon - Hakiki, Nurul; Sarka, I Ketut; Harinita, Ni Luh Gede; Tresna, I Dewa Gede Agus; Widiana, I Nyoman; Sudirgayasa, I Gede Putu; Putrayasa, I Made Wira (Universitas Triatma Mulya, 2025)
Bali is famous not only for its culture but also for its distinctive traditional cuisine. One of the most popular dishes is ayam betutu, a Balinese dish that is in high demand by tourists. Consumer decisions to buy chicken betutu at Ayam Betutu Khas Gilimanuk restaurant are influenced by various factors, such as affordable prices, distinctive flavours, restaurant identity, packaging, food quality, service, and size variations. This study aims to identify factors that influence purchasing decisions, visitors' perceptions of ayam betutu culinary development strategies, and adaptation strategies in serving the dish. The research method used a sociology of tourism approach with data collection techniques through interviews with visitors, owners, cooks, and waiters. Data were analysed using SWOT analysis method and Likert scale. The results showed that information technology-based promotion strategies, adaptation of forms, ingredients, flavours, and cooking techniques are important steps in developing the attractiveness of ayam betutu as a culinary destination.